A 'GLoRy' Battle for Cotton against Fusarium. (July 2021) - Wang, Ping; Mormile, Brendan; He, Ping
Abstract : Glutamate receptor-like (GLR) proteins are ligand-gated ion channels regulating various plant physiology. They function as calcium channels in plant immunity and mediate long-distance defense to herbivores. A recent study by Liu et al. identified a cotton GLR as a noncanonical resistance protein to Fusarium wilt, expanding the paradigm of GLR functions in plant immunity.